Refuting the alleged transmission of concepts of Greek thinking to Arabic grammar = Menyangkal konsep tatabahasa Arab dipengaruhi pemikiran Greek - Yaacob, Solehah@Nik Najah Fadilah (International Islamic University Malaysia, 2011)
The study aims to provide a critical examination of the influence of concepts from Ancient Greek thinking on Arabic grammar. In order to determine whether and to what degree Arabic Grammar was influenced by ancient Greek, the researcher adopts a theoretical and analytical approach based on linguistic studies conducted by authors like J. Weiss, H. Fleisch, M.G. Carter and G.Troupeau. The study seeks to debunk or refute previous studies on the issue of alleged transmission of Greek grammatical concepts into Arabic grammar. In order to reach a balanced and objective judgment on this issue, the linguistic corpus and the historical background of transmission shall be analyzed.